2015
DOI: 10.1158/0008-5472.can-14-1458
|View full text |Cite
|
Sign up to set email alerts
|

A Noninvasive Procedure for Early-Stage Discrimination of Malignant and Precancerous Vocal Fold Lesions Based on Laryngeal Dynamics Analysis

Abstract: About two thirds of laryngeal cancers originate at the vocal cords. Early-stage detection of malignant vocal fold alterations, including a discrimination of premalignant lesions, represents a major challenge in laryngology as precancerous vocal fold lesions and small carcinomas are difficult to distinguish by means of regular endoscopy only. We report a procedure to discriminate between malignant and precancerous lesions by measuring the characteristics of vocal fold dynamics by means of a computerized analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…The carcinoma transformation rate of vocal leukoplakia is 8% [3]. Dysplasia is not discovered in 50% clinical laryngeal leukoplakia patients with the histopathological assessment [4]; however, some of these patients will suffer carcinoma transformation at some point during their entire lives [3].…”
Section: Introductionmentioning
confidence: 99%
“…The carcinoma transformation rate of vocal leukoplakia is 8% [3]. Dysplasia is not discovered in 50% clinical laryngeal leukoplakia patients with the histopathological assessment [4]; however, some of these patients will suffer carcinoma transformation at some point during their entire lives [3].…”
Section: Introductionmentioning
confidence: 99%
“…For HSI‐interpretation, the synchronous or asynchronous movement of the vocal folds was considered as the most essential parameter. In a previous study it was found that in malignant lesions the affected vocal fold moves towards the glottic midline earlier than the healthy vocal fold. This could be explained by the fact that cancers per definition disrupt the basement membrane and often invade the underlying musculature and thus make the vocal fold stiffer.…”
Section: Resultsmentioning
confidence: 97%
“…White light imaging, NBI and HSI seem complementary rather than competitive optical tools in the diagnostic workup of laryngeal lesions. While NBI is focusing on the morphological appearance of lesions by showing their superficial extension and changes in vascularization [1,8,11,12,17,18,39], HSI is focusing on vocal fold function [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters considered were chosen because (1) they are already frequently applied in daily clinical routine and in other studies, (2) they reflect different characteristics of the vocal folds and glottis dynamics, and (3) they are computed on different spaces (spectral and time space of the GAW). Although there are certainly more objective parameters being used in HSV analysis [8, 23, 29], the consideration of all possible HSV parameters would go far beyond one study. The primary goal of our study was to determine if there is a frame rate dependence among the HSV parameters.…”
Section: Methodsmentioning
confidence: 99%